If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(-5+x)=12
We simplify the equation to the form, which is simple to understand
-3(-5+x)=12
Reorder the terms in parentheses
+(+15-3x)=12
Remove unnecessary parentheses
+15-3x=+12
We move all terms containing x to the left and all other terms to the right.
-3x=+12-15
We simplify left and right side of the equation.
-3x=-3
We divide both sides of the equation by -3 to get x.
x=1
| 24*3= | | 9640=x^2+40x+40 | | .3*24= | | b+8+5b=180 | | (-6.7x+3)(-6)= | | -2(3a+4)= | | 45/150= | | 150/45= | | 26x*276=x*108 | | 25x*276=x*108 | | (u+9)(u+7)=99 | | 24*0.3= | | k^2=-10k | | m^2=-6m | | m(m-8)=-12 | | 3a-7+5b=180 | | 0.6w-0.4=-4+w | | 6x^2+40x-1000=0 | | 5c+12=8c+10.62 | | 25x+276=x-108 | | 9.7m-8.7=28.16 | | 6.9y+4.61=-34.03 | | 100=10x*10 | | 3n^2+6n-73=0 | | 0.5x=-65 | | -80.2+n=-85 | | 12x^2-6x+15= | | (-6.3x+5)(-4)= | | d*0.3=9 | | X^2+3/5-1=0 | | 9p+.75d=75 | | 12z^2+5z-3=0 |